Site-specific O-Glucosylation of the Epidermal Growth Factor-like (EGF) Repeats of Notch: EFFICIENCY OF GLYCOSYLATION IS AFFECTED BY PROPER FOLDING AND AMINO ACID SEQUENCE OF INDIVIDUAL EGF REPEATS - Takeuchi, Hideyuki (American Society for Biochemistry and Molecular Biology, 2012)
O-Glucosylation of epidermal growth factor-like (EGF) repeats in the extracellular domain of Notch is essential for Notch function. O-Glucose can be elongated by xylose to the trisaccharide, Xylα1–3Xylα1–3Glcβ1-O-Ser, whose synthesis is catalyzed by the consecutive action of three glycosyltransferases. A UDP-glucose:protein O-glucosyltransferase (Poglut/Rumi) transfers O-glucose to serine within the O-glucose consensus. Subsequently, either of two UDP-xylose:glucoside xylosyltransferases (Gxylt1 or Gxylt2) transfers xylose to O-glucose. Finally, a UDP-xylose:xyloside xylosyltransferase (Xxylt1) transfers xylose to Xylα1–3Glcβ1-O-EGF. Our prior site-mapping studies demonstrated that O-glucose consensus sites are modified at high but variable stoichiometries in mouse Notch1 and identified a novel glycosylation site with alanine in place of proline, suggesting a revised, broader consensus sequence (CXSX(P/A)C). Here we examined the molecular basis for this site specificity. A panel of EGF repeats from human coagulation factor 9 (FA9), mouse Notch1, and Notch2 were bacterially expressed and purified by reverse phase HPLC for use in in vitro enzyme assays. We demonstrate that proper folding of EGF repeats is essential for glycosylation by Poglut/Rumi, that alanine can substitute for proline in the context of coagulation factor 9 EGF repeat for O-glucose transfer, confirming the new consensus sequence, and that positively charged residues within the O-glucose consensus sequence reduce efficiency of glycosylation by Poglut/Rumi. Moreover, proper folding of EGF repeats is also important for the activities of Gxylt1, Gxylt2, and Xxylt1. These results indicate that protein folding and amino acid sequences of individual EGF repeats fundamentally affect both attachment and elongation of O-glucose glycans.